Odpowiedzi

2009-10-27T11:29:01+01:00
1]=-6√3-4√3+20√3=10√3 2]=8√5+14√5-12√5=10√5 3]=√2+2√2+2√3+4√2=7√2+2√3 4]=5√3+4√3+3√3+√3=13√3 5]=5√7-10√7+24-7√7=-12√7+24 6]=-3√10+5√10-4√10-7√10=-9√10
2009-10-27T11:39:30+01:00
1) -6√3 - √48 + 2√300=-6√3-√3*16+2√3*100=-6√3-4√3+20√3=10√3
2) 8√5 + 2√245 - 3√80=8√5 +2√5 *49-3√5 *16=8√5 +14√5 -12√5 =10√5
3) √2 + √8 + √12 + √32=√2+√2*4+√4*3+√2*16=√2+2√2+2√3+4√2=7√2+2√3
4) √75 + √48 + √27 + √3=√3*25+√3*16+√3*9+√3=5√3+4√3+3√3+√3=13√3
5) √175 - √700 + √576 - √343=√7*25-√7*100+√4*144-√7*49
=5√7-10√7+24-7√7=12√7+24=12(√7+2)

6) -√90 + √250 - √160 - √490= -√9*10+√25*10-√16*10-√49*10=
-3√10+5√10-4√10-7√10=-9√10
2009-10-27T15:48:36+01:00
A) -18-4√3+12∫3=-18-4+12∫3=-10∫3
b)8∫5+14∫5-4∫5=8+14-4∫5=8+10∫5=18∫5
c)∫2+2∫2+3∫2+4∫2=2+2+3+4∫2=11∫2
d)5∫3+4∫3+3∫3+∫3=5+4+3∫3=12∫3
e)nie wiem
f)3∫10+5∫10-4∫10-7∫10=3+5-4-7∫10=-3∫10